(Evaluation of Health Services using Total Quality Management in Sudan during the period 2002-2012 (Khartoum State Hospital Case Study - Yahya, Hamza Abdullah Abdul Rahman; Muhammad, Abu Bakr doaa albeit Abu Bakr; Younes, Abdel Shafie Mohammed abkar (Journal of Economic, Administrative and Legal Sciences, 2017)
This study dealt with the evaluation of health services , in using of Total Quality Management (TQM) in sudan , during the period 2002-2012 . The problem of the study was the face of health service organization in sudan for many of the administrative challenges that caused the failure and inability to grow and that the lack of total quality management in these organizations. The study answered the following question: what is the role of evaluating the total quality of health services? what is the role of tangibles in evaluation of health services ? what is the role of reliability in evaluation of health services ?. The importance of study originated from the great role it plays in the delivery of health services in sudan , through information and data analysis for use .The study aimed to find our whether there is arelationship between the aspects of TQM and the evaluating of health services , and know the criteria for evaluating the health services , and the extent of adoption of the hospitals to TQM criteria , the study adopted the historical and the descriptive analytical methods .The study found anumber of findings , the most important were :and the need to modernize the current medical equipments , and the need to find arelationship between the dimension of the status queue and the evaluation of health services , as there is no relationship between actual status and evaluation of health services . the study came out with anumber of recommendation including that : the hospital administration should update the current medical equipments , the hospital administration must abide its duty towards patients in the provision of health services and setting atimetable for patients that sets deadlines to provide the apentic services to them .
Keywords: quality; comprehensive quality management; credibility; health services; efficiency